MODEL KOMUNIKASI BISNIS DALAM BERWIRAUSAHA KULINER PASCA PANDEMI COVID-19 PADA UMKM KOTA DEPOK - Hiswanti, Hiswanti; Bachtiar, Alfan; wukir, Iswahyu Prana; Misnan, Misnan; Suandi, Fikri (Universitas Bina Sarana Informatika, 2024)
The theory of the social construction of reality and the theory of the social construction of mass media are still partially discussed. Several previous pieces of research have not yet correlated, elaborated, or synthesized from the theoretical aspect. Even though much has been said about the social construction of reality, media consumers are heavily influenced by media